TRANSLATOR'S HABITUS AND TRANSLATION IDEOLOGY: TRANSLATING THE CONCEPT OF CAPITALS IN THE NOVEL BUMI MANUSIA BY PRAMOEDYA ANANTA TOER - Wahyuningsih, Neneng Sri (Universitas Islam Sumatera Utara (UISU), 2023)
This study examines the relationship between the translator's habitus and translation ideology in translating the concept of capitals that exists in the two main characters in the novel Bumi Manusia by Pramoedya Ananta Toer. This research uses a descriptive qualitative method by taking a case study of two chapters in Bumi Manusia and its translation in English. The study found 30 expressions containing modals in the two main characters in chapters 5 and 7. The translation procedures carried out by the translator consist of standard translation (one datum), transference (15 data), modulation (four data), literal (six data), addition (one datum), contextual equivalence (two data), and paraphrasing (one datum). From Minke's character, there were 11 translations with the ideology of domestication and seven data of foreignization; and from Nyai Ontosoroh's character, only one expression that was translated domestically, and the other 11 data were foreignized. Therefore, 12 out of 30 data, i.e., 40%, were translated with domestication ideology, while 18 out of 30 data or 60% were translated with foreignization ideology. In conclusion, a translator's habitus influenced his way of translating which automatically directed his translation ideology.